The Effect of Variations in Temperature and Humidity Based on OIML R 111-1: 2004 on the Calibration of F1-Class Weighing Scale Weight Standards - Tri Surawan; Rudy Yulianto; Nani Kurniawati; Fogot Endro Wibowo; Tony Sutrisno (Green Publisher Indonesia, 2026)
The Effect of Variations in Temperature and Humidity Based on OIML R 111-1: 2004 on the Calibration of F1-Class Weighing Scale Weight Standards investigates the accuracy of mass measurement, which is an important aspect of modern commerce, particularly for consumer protection and the maintenance of orderly trade. The OIML R 111-1:2004 standard defines requirements related to environmental conditions and physical characteristics for weight standards and calibration processes. This study aimed to analyze the effects of temperature and humidity variations on the calibration results of F1-class weights based on the OIML R 111-1:2004 standard. The research was conducted by observing standard and test mass readings within a temperature range of 18.0 °C to 25.0 °C and relative humidity (RH) levels between 50% and 60%. The data were analyzed using a two-way analysis of variance (ANOVA) to test the significance of individual factors and their interaction effects between environmental variables. The results showed that increasing temperature linearly increased the balance reading values while decreasing air density from 1.19206 kg/m³ to 1.16081 kg/m³. Statistical analysis using ANOVA confirmed that variations in temperature and humidity had a highly significant effect on calibration results, with a p-value of 5.27 × 10⁻¹³⁴ under conventional mass conditions. The interaction between temperature and humidity was also significant, with an F-value of 1001.78, far exceeding the critical F-value of 1.84. Despite environmental fluctuations, conventional mass correction methods remained effective in maintaining result stability, with very low variance values in the range of 10⁻¹⁰ to 10⁻¹¹. All conventional mass values remained below the Maximum Permissible Error (MPE) limit of 5.0 mg for a nominal 1 kg F1-class weight. This study concludes that the application of buoyancy correction in accordance with OIML R 111-1:2004 is essential to maintain calibration accuracy under varying environmental conditions that significantly affect measurement results.